Impact of the COVID-19 pandemic on patient perceptions of the quality of their cancer care. Issue 28 (1st October 2022) - Powis, Melanie Lynn; Alibhai, Shabbir M.H.; Berlin, Alejandro; Sutradhar, Rinku; Singh, Simron; Hack, Saidah; Krzyzanowska, Monika K.
Abstract : 286 Background: COVID has had a significant impact on how cancer care is delivered. Numerous modifications to care aimed at reducing in-person visits, and mitigating potential issues with staff and resource shortages were introduced, including the implementation of virtual visits. As many of the changes to cancer care are likely to persist beyond the pandemic, we undertook a survey to understand patients' perceptions of the impact of the pandemic on the quality of cancer care that they received. Methods: We developed an electronic survey guided by the Picker Institute's eight principles of patient-centred care. Patients >18 years of age with a valid email address on file who have had a visit in the gastrointestinal clinic at Princess Margaret Cancer Centre (PM) in Toronto, Canada between 03/2020 and 05/2021 were recruited via email invitation in 10/2021 to anonymously participate. Logistic regression models were utilized to examine adjusted associations between demographic and clinical variables, and reporting a negative perception of care. Results: The response rate was 17.1% (438/2563); after excluding responses from those who are no longer patients and incomplete responses, 358 responses were included in the final analysis. Respondents were most commonly >65 years of age (46.6%), male (48.6%), college/university educated (55.5%) and in follow-up phase of their disease (54.2%). Approximately half of respondents (56.1%) had some experience with care at PM prior to the pandemic, while the remaining patients were referred during. Most respondents (76.3%) indicated that, overall, they were satisfied with the care they received during COVID. Compared to patients who experienced care at PM prior to the pandemic, patients referred during COVID were 2.5 times more likely to believe that patients received worse care during COVID than those treated prior (OR: 2.42; 95% CI: 1.08-5.44). Most respondents (69.5%) reported that virtual appointments positively impacted the quality of their cancer care. Adequacy of emotional support was the most negatively perceived dimension of patient-centred care, whereby 18.7% of patients felt they were provided with inadequate information on support services available to them, and 17.6% felt that they had received inadequate support. Relative to those in follow-up, patients with a newly diagnosed cancer were more likely to report receipt of inadequate emotional support (OR: 5.69; 95% CI: 2.18-14.82). Conclusions: Most patients reported being satisfied with the quality of care provided to them during COVID and reported a positive impact of virtual appointments on their care. Future quality improvement efforts should focus on how to improve dissemination of information on available support services and access to appropriate emotional supports, particularly for newly diagnosed patients.